Open Source Software Use in Libraries: Implications for Social Justice? - Singh, Vandana (Qualitative and Quantitative Methods in Libraries, 2017)
This paper starts an initial discussion into relating use of open source software and technology for social justice via libraries. A thorough literature review of social justice, role of libraries in social justice and open source and its relation to social justice by libraries is presented. Experience based evidence of use of open source software in libraries for the purpose of achieving social justice is provided. Recommendations for libraries and future collaborations are also outlines.